The Protection of The Right to Health Services for The People With mental Disorders Especially in Yogyakarta Based on Law Number 18 of 2014 Mental Health - Odilia Esem; Endang Wahyati; Tjahjono Kuntjoro (Universitas Katolik Soegijapranata Semarang, 2018)
The rights to health care were basic rights that were subjected to every person, including people having mental disorders (ODGJ). The ODGJ had the same opportunity to get health services through the mental health facilities, mental health workers, mental health supplies provided by the government. This study aimed to know the regulation on ODGJ’s health service rights, the implementation of the protection of ODGJ’s rights to health services and the factors affecting the implementation of the protection of ODGJ’s rights to health services. The research was conducted at the Special Province of Yogyakarta (DIY) namely in Grhasia Mental Hospital, Panembahan Senopati General Hospital of Bantul and Mergangsan Public Health Center. This research applied a socio-legal approach having an analytical-descriptive specification. The data gathered were primary and secondary data that were obtained by field studies and literature study. The field studies were conducted by interviews with the directors of the hospitals, Head of the Public Health Center, Head of Health Office, and ODGJ’sfamilies. The data were then qualitatively analyzed. The results of the study showed that there had been provisions ODGJ’s rights to health services based on the Republic of Indonesia’s Constitution, Act Nr. 39 of 1999 on Human Rights, Act Nr. 36 of 2009 on Health, Act Nr.18 of 2014 on Mental Health, Minister of Health’s Regulation Nr. 43 of 2016 on Minimum Service Standard in Health Sector, Yogyakarta Special Province’s Regulation Nr. 1 of 2014 on Vagrant and Beggars and Yogyakarta Governor’s Regulation Nr. 81 of 2014 on Guidance for Stocks Placement Prevention. Health services for ODGJ had been accomplished in Yogyakarta Province by providing health facilities at both the hospitals and the public health center as well. However, the protection of ODGJ’srights to health services had not been optimally fulfilled. It was influenced by several factors namely juridical, social and technical factors.